The Effect of Anxiety Level to The Menstrual Cycle on DIII Midwifery Student at STIKes Nani Hasanuddin Makassar - Dahniar Dahniar; Indah Yun Diniaty Rosidi (STIKes Patria Husada Blitar, 2022)
Adolescence is psychologically a period of transition from childhood to adulthood. Menstruation is an important event in the life of a young woman. For this reason, young women need to recognize their bodies, what will happen, so that they are not surprised or frightened when their first menstruation arrives. The menstrual cycle is important as a reproductive function that carries out preparation for conception and pregnancy.The purpose of this study was to determine the effect of anxiety levels on the menstrual cycle in DIII Midwifery students of Stikes Nani Hasanuddin Makassar. This research uses quantitative analytic method , with a cross sectional approach . The population in the study of all students of the 2019 batch was 3-7 respondents and the sample used was 37 respondents with a total sampling technique. Result: There is no correlation between anxiety level and menstrual cycle in DIII Midwifery students of STIKes Nani Hasanuddin Makassar. The large Odds Ratio (OR) on the test results is 0.622, it is most likely that the risk of disruption of the menstrual cycle of DIII Midwifery students if experiencing severe anxiety is 0.622 times compared to DIII Midwifery students who only experience moderate anxiety.